The Training 3 in 1 Making Fashion Embellishment with Hand Sewing Tools Batch-X (Gold Thread Embroidery) in Balai Diklat Industri Padang - Sasmita, Sasmita; Natsir, MHD (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
This research is written based on the 3 in 1 Training for Making Fashion Embellishments with Hand Sewing Tools Batch X (Gold Thread Embroidery) which aims to improve skills and create jobs in the field of embroidery and fashion aimed at people who need training so that the skills they have can be officially recognized in the form of certificates. The purpose of this study is to describe the implementation process of the Training 3 in 1 Making Fashion Embellishments with Hand Sewing Tools Batch X (Gold Thread Embroidery) in conducting training. This research uses a qualitative approach, with a case study research method. The data sources in this study are the Head of the Training Organizer as the research subject and the head of the training, instructors and participants as research informants. The data collection techniques used were observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation and drawing conclusions. Data validity techniques are using source triangulation, technique triangulation, and time triangulation. The results showed that the skills training process starts from 1) Planning; 2) Implementation; 3) Assistance; and 4) Evaluation.